Clinical profile and dermoscopic findings in alopecia areata - Aswin Sreevas O; Mary Vineetha; Aswini R (Asian Journal of Medical Sciences, 2022)
Background: Alopecia areata (AA) is a common, chronic, and inflammatory disease that causes non-scarring hair loss. Dermoscopy can be used not only to diagnose AA and differentiate other causes of patchy alopecia but can also be a useful tool in assessing the severity of the disease. Aim and Objectives: The aim of the study was to study the clinical profile, various dermoscopic findings, and correlation between different dermoscopic findings and disease severity of AA. Materials and Methods: It was a cross-sectional descriptive study including clinically diagnosed cases of AA attending the outpatient department of dermatology. A detailed history and clinical examination was done along with dermoscopy of lesion and the patterns were noted. Results: A total of 117 patients were included in study. About 44% patients had mild AA, 48% had moderate, and 8% had severe alopecia. Patients with atopy and family history had an early onset of disease. Family history, presence of diabetic mellitus, and nail changes were associated with severe disease. The most common dermoscopic finding noted in our study was black dots followed by short vellus hairs, broken hairs, yellow dots, and tapering hairs. Yellow dots correlated positively with severity of AA while black dots, broken hairs, and short vellus hairs correlated negatively with the severity of AA. There was no relation between tapering hairs and severity of AA. Conclusion: AA is a disease of younger age. Black dots are the most common dermoscopic findings and along with this other patterns can be useful in diagnosis and assessment of severity of disease.